EVALUASI PENGEMBANGAN EKOWISATA DESA BUDAYA KERTALANGU DI DESA KESIMAN KERTALANGU KOTA DENPASAR - Sukarji Putra, Made Agus; Adnyana Manuaba, IB; Sunarta, I Nyoman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 5 No 1)
The purpose of research is to know the ideal pattern for eco-tourism which should develop at Kertalangu Cultural Village, in effort to conserve the rich field area from displace farm function to be tourist facility. Kertalangu Cultural Village have the potential culture and nature which become separate fascination for tourism, such as: jogging track, agro-tourism, fishing ground area, culiner, culture of ritual religious, artistry of dance and tabuh, and the other support facilities. Kertalangu Cultural Village located at Kesiman Kertalangu Village in Denpasar is compatible to be developed as the eco-tourism area because have fulfilled of principle for eco-tourism development. Five principles from nine especial principle for eco-tourism development have been fulfilled as mention in eco-tourism workshop in sanur on 3 – 5 September 2002, such as: has the awareness sense, comitment and responsibilty for nature conservation and cultural heritage, sensitive sense and respecting the social culture values and religious tradition of local community, adhering the exist law and regulation, the development based on approval of local community, well-balance and compatible management system as according to Tri Hita Karana concept. On the other hand, four principles which has not fulfilled yet, are: empowered and optimalisation of community participation and give the contribution continually to local community, provide the understanding which give the opportunity for tourist to enjoy the nature and improving their willingness to aware with nature surrounding, consistently give the satisfaction for consumer, marketed and promoted in accuratly according with their expectation (responsible marketing).
Keywords: Evaluation, Kertalangu Cultural Village, Kesiman Kertalangu Village, Nine Principles Idea of Eco-tourism.